Teachers’ Efforts in Developing the Creativity of New Students through Calligraphy Extracurricular Activities at Pondok Pesantren Wali Songo - Arsyad Ali Fahmi (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2025)
His study explores how teachers aim to enhance the creativity of new students through calligraphy extracurricular activities, using a qualitative approach. The research reveals obstacles faced by new students at PP. Wali Songo Sukajadi, including boredom with teaching methods, inadequate facilities, and lack of guidance due to teacher inexperience. To address these issues, the Bakat Minat committee introduced an expert calligraphy teacher in 2024 to provide guidance and prevent student disinterest. Through dedicated efforts, the teacher successfully impacts the creativity development of new students. The study focuses on assessing the teacher's strategies in fostering student creativity through calligraphy extracurricular activities, employing descriptive analysis methods including observation, interviews, and documentation. The data analysis process involves data collection, reduction, presentation, validation, and drawing conclusions.